2016
DOI: 10.5897/ajmr2016.8038
|View full text |Cite
|
Sign up to set email alerts
|

-Fructofuranosidase production by Aspergillus versicolor isolated from Atlantic forest and grown on apple pomace

Abstract: This study explores the production and characterization of an extracellular β-fructofuranosidase (FFase-I) by Aspergillus versicolor newly isolated from Atlantic Forest-Brazil. The β-fructofuranosidase production by fungus, after the optimization process using central composite design and response surface methodology, showed that 3% (w/v) apple pomace, an initial pH 7.5, and 12 days of cultivation provided the best conditions. The β-fructofuranosidase (FFase-I) was purified from the crude extract by 75% (NH 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Another fungus A. niger PSSF21, which was isolated from agricultural fields, was reported to produce maximal FFase at only 19.1 U/mL using sugarcane molasses as carbon source (Reddy et al 2010). More recently, a newly fungus A. versicolor isolated from Atlantic Forest-Brazil could produce 48.17 U/mL FFase using apple pomace as carbon source after 8 d cultivation under the optimized condition (Dapper et al 2016). These results showed that the low-cost carbon sources could be used for production of FFase and hence reduce the FOS production cost.…”
Section: Discussionmentioning
confidence: 99%
“…Another fungus A. niger PSSF21, which was isolated from agricultural fields, was reported to produce maximal FFase at only 19.1 U/mL using sugarcane molasses as carbon source (Reddy et al 2010). More recently, a newly fungus A. versicolor isolated from Atlantic Forest-Brazil could produce 48.17 U/mL FFase using apple pomace as carbon source after 8 d cultivation under the optimized condition (Dapper et al 2016). These results showed that the low-cost carbon sources could be used for production of FFase and hence reduce the FOS production cost.…”
Section: Discussionmentioning
confidence: 99%
“…Conventionally, polysaccharides are produced using sucrose as substrate, and enzymes such as β-fructofuranosidase and fructosyltransferase (de la Rosa et al, 2019). However, nowadays, more profitable processes involve fruits by-products and microorganisms such as Aspergillus versicolor (Dapper et al, 2016) or Aspergillus flavus (Ganaie et al, 2017). The agro industrial wastes which can be exploited for this purpose are those rich in sucrose: peels (agave mango, banana, pineapple, orange, etc.…”
Section: Industrial Applications Of Valuable Compounds Obtained From mentioning
confidence: 99%
“…), leaves (banana, etc. ), or pomaces (apple grape pomace) (Gnaneshwar Goud et al, 2013;Dapper et al, 2016). Fruits pomace can be also used to obtain pectin (used both in cosmetic and in food industry) (Barreira et al, 2019) or bioethanol, hydrogen or methane via anaerobic fermentation (Evcan and Tari, 2015).…”
Section: Industrial Applications Of Valuable Compounds Obtained From mentioning
confidence: 99%
“…), pomaces (like apple pomace and grape pomace) and coffee processing by-products (coffee pulp, coffee husk and coffee spent grain) (Ali, 2011, pp. 48-54;Arfelli et al, 2016;Ghazi et al, 2006;Gnaneshwar Goud, Chaitanya, & Reddy, 2013;Mehta & Duhan, 2014;Muñiz-Márquez et al, 2016, 2019Mussatto et al, 2013;Ruiz et al, 2014;Smaali et al, 2012).…”
Section: Agro-industrial By-products As Bioresource For Biotechnologimentioning
confidence: 99%
“…Due to all its nutrients, molasses have been exploited for enzyme production. Several reports have been evaluating different agro-industrial by-products as carbon sources for the production of invertase, such as sugar cane molasses, among other wastes (Ohara et al, 2015;Arfelli et al, 2016). Reddy, Reddy, and Sulochana (2010) also reported the use of sugarcane molasses for FFase production with A. niger PSSF21.…”
Section: Molassesmentioning
confidence: 99%